Impact analysis: electronic logging devices in the transportation industry. (14th January 2021) - Koomen, Jonathan M.; Fenik, Anton P.
A disruptive digital transformation in the transportation industry recently arrived in the form of an electronic logging devices (ELDs), which serves to replace paper and pen logging of driving hours. The government mandate went into effect in December of 2017 with touted benefits primarily in the form of safety improvements. This research explores the first 12 months of this transformation by interviewing professionals affected by the mandate and by reviewing the still fresh and scarce literature. The results point to short and long-term challenges with which the fleet operators must grapple with before realising the value proposition promised by this digital transformation. The paper offers to practitioners structured summaries of the findings and recommendations for successful implementation of ELDs in order to become fully compliant with the law. Policymakers can gain insights from this study to understand weaknesses of the mandate in the current form. Altogether, this paper brings awareness of benefits and costs of the mandate to all affected stakeholders.